Determinants of the Choice of Preferred Providers among the Publicly Insured in Chile: an Empirical Analysis - Henríquez H., Ricardo (Estudios de Administración, 2000)
This paper analyses the determinants of the choice of provider among the publicly insured in Chile. The focus is on the Preferred Provider System (PPS) where public insured can opt for a more consumer-oriented environment subject to a higher level of copayments. Using a model of expected utility gain we develop a logit analysis based on a large multipurpose survey, the Encuesta de Caracterización Socioeconómica Nacional, CASEN 1992 (National Survey for Socioeconomic Characterisation). We make use of several socio-economic, demographic and access variables in our econometric estimation. As a whole, our results adjust to the hypotheses formulated. Among others, individuals’ income, the relative value of copayments, waiting time and zone of residence emerge as the most relevant determinants in the decision process. The positive effect of income would indicate some degree of segmentation within the public system, while the impact of the relative value of copayments shows that user charges can act as an important deterrent for some individuals. The unexpected negative effect of waiting time, included in our estimation as a provider’s attribute, would suggest certain level of captivity in the sense that some individuals have no real choices but purely public provision. The result for zone of residence indicates that rural residents are less likely to choose preferred providers than urban residents. This result is explained by the spatial distribution of preferred providers who tend to cluster in urban areas.